Gigitiruan sebagian imidiat untuk memperbaiki estetik gigi anterior yang mengalami kelainan periodontal - Ike Damayanti Habar (Journal of Dentomaxillofacial Science, 2007)
The treatment of immediate partial denture has the objective of enhancing the aestheticsof the condition and position of protrusive anterior teeth because of periodontal disorderthat would improve the face appearance. This case study was carried out on a 32-year oldfemale patient with protrusive and very mobile anterior teeth that obstruct the lipsclosure. The diagnosis of patient was dental protrusion in upper and lower mandiblealong with diastema as the result of rapidly progressive periodontitis. The treatmentimplemented was the construction of immediate partial denture with extraction of theanterior teeth. After insertion, control was performed at 24 hours, three days and sevendays. It appeared that aesthetics, occlusion, articulation, retention and stabilization wasvery good.